Peningkatan keterampilan membaca pemahaman melalui strategi pembelajan know want learn (KWL) pada peserta didik kelas IV sekolah dasar - Estu Ginarsih Ayu Puspita; Retno Winarni; Muhammad Ismail Sriyanto (Universitas Sebelas Maret, 2020)
This research aims to improve reading comprehension skills with Know Want Learn learning strategies. The subjects of this research were 31 students in class IV Karangasem II Elementary School Surakarta in the academic year 2019/2020. This study uses data collection techniques such as observation, interviews, documentation and reading skills tests that are tested with content validity, triangulation of data sources and triangulation of techniques. The results that has been obtained will be processed by data analysis techniques from Miles and Huberman. From the results before the implementation of the Know Want Learn strategy, classical completeness was only 12.9% (only 4 students), then after the implementation of the Know Want Learn strategy the results of reading comprehension skills increased by 48.39% (15 students) in the first cycle and 82.2% (26 students) in the second cycle. So, the Know Want Learn strategy can improve reading comprehension skills in grade IV students of SD Negeri Karangasem II in the 2019/2020 school year. The teacher can apply this know want learn strategy to reading comprehension learning in elementary schools, especially fourth grade.